Communications via the Small Leucine-rich Proteoglycans: Molecular Specificity in Inflammation and Autoimmune Diseases. (December 2020) - Zeng-Brouwers, Jinyang; Pandey, Sony; Trebicka, Jonel; Wygrecka, Malgorzata; Schaefer, Liliana
Inflammation is a highly regulated biological response of the immune system that is triggered by assaulting pathogens or endogenous alarmins. It is now well established that some soluble extracellular matrix constituents, such as small leucine-rich proteoglycans (SLRPs), can act as danger signals and trigger aseptic inflammation by interacting with innate immune receptors. SLRP inflammatory signaling cascade goes far beyond its canonical function. By choosing specific innate immune receptors, coreceptors, and adaptor molecules, SLRPs promote a switch between pro- and anti-inflammatory signaling, thereby determining disease resolution or chronification. Moreover, by orchestrating signaling through various receptors, SLRPs fine-tune inflammation and, despite their structural homology, regulate inflammatory processes in a molecule-specific manner. Hence, the overarching theme of this review is to highlight the molecular and functional specificity of biglycan-, decorin-, lumican-, and fibromodulin-mediated signaling in inflammatory and autoimmune diseases